Longitudinal follow‐up of biopsy‐proven small fiber neuropathy. Issue 4 (8th August 2019) - MacDonald, Steven; Sharma, Tara L.; Li, Jianbo; Polston, David; Li, Yuebing
Abstract: Introduction: Little is published on the prognosis of small fiber neuropathy (SFN). Methods: A retrospective analysis of 101 patients with biopsy proven SFN. Results: Study participants included 87 patients with length‐dependent SFN and 14 patients with non–length‐dependent SFN. The average duration of symptoms was 3.2 years prior to SFN diagnosis, and the average follow‐up duration after diagnosis was 6.2 years. Neuropathic pain was present in 98% of patients and in 84.2% of patients at the final visit. The average total number of pain medications ever used was 4.4 per patient. Signs of autonomic dysfunction were initially present in 24.8% of patients, but improved in most. Large fiber involvement was seen in 11.9% of patients. Small fiber neuropathy affected employment and ambulation status in 5.3% and 6.3% of patients, respectively. Discussion: Small fiber neuropathy tends to be stable and rarely affects ambulation and employment status. Effective pain control remains a challenge.